DIGITAL PAYMENT PROCESS AND DOCUMENT FILLING OPERATIONAL MANAGEMENT - Yudo Wibisono; Elysabeth Liu; Obrin Alkautsar; Besar Agung Martono (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
This article discusses the document management process for billing documents from vendors for payment processing. Since there was a pandemic in March 2020 to maintain sterilization, direct contact with people and documents is strictly avoided. One of them is billing documents, which were usually done via hard copy before the pandemic to be submitted to the Department of Finance. Since the pandemic, there has been a change in billing operations, where documents are no longer made in hard copy, but through soft copy. An important point in doing through soft copy is the legitimacy of documents or avoiding document falsification, so that it can harm the company. As well as how to take advantage of digitizing billing patterns so that you can save on document storage. This article is important considering that the digitization process must maintain the validity/validity of documents and so that they can comply with the rules related to archive management. The purpose of this research is to find out the operationally standardized process flow that is standardized within the company and the savings on document storage costs that have been carried out. This research was conducted at a company engaged in the energy sector with offices in South Jakarta. The research method used is a qualitative method with primary and secondary data sources. The conclusion of this research is that a company is agile for changes, so that operations can adjust by utilizing online/digital media to achieve process efficiency and effectiveness